Expressing community through freedom market and visual connections. (2nd January 2017) - Larson, Joanne; Hanny, Courtney; Duckles, Joyce; Pham, Hoang; Moses, Robert; Moses, George
ABSTRACT: Building on a long-term university/community research partnership, this article examines how different ways of conceptualizing, interpreting, and producing murals impacted how an urban community saw itself. Using a participatory action research design, university researchers worked alongside community researchers to ethnographically document the transformation. Findings indicate that the mural project constructed pathways for building relationships and community in ways that made neighborhood transformation possible. The mural project embodied this transformative goal by providing a space where people gathered with shared attention to talk and to envision how their lives and their community could be different.